Measles-mumps-rubella-vaccination at 6 months of age induces measles-specific T cell responses: a randomized controlled trial - Buus, Søren; Vittrup, Dorthe Maria; Schmidt, Jonas Damgård; Jensen, Andreas; Stryhn, Anette; Stensballe, Lone Graff (Frontiers in Immunology, 2025)
BackgroundMeasles is a highly contagious viral disease, particularly severe in infants. Protection in early life is provided by maternally transferred antibodies, but this period is shorter in infants of previously vaccinated mothers (PVMs) compared to infants of previously measles-infected mothers (PIMs). Earlier measles-mumps-rubella (MMR) vaccination may compensate for this. To evaluate immune responses, 6-month-old infants were randomized to receive early MMR or placebo. This study reports the cellular immune outcomes and summarizes serological and T-cell responses.MethodsA double-blind, randomized trial involved 6540 Danish infants aged 5–7 months, eligible if birth weight exceeded 1000 grams and gestational age was ≥32 weeks. Participants were randomized 1:1 to receive M-M-RVaxPro or placebo. Blood samples were collected before intervention, four weeks after intervention, and four weeks after routine MMR at 15 months. Peripheral blood mononuclear cells (PBMCs) were prepared, and an IFN-γ specific ELISpot assay measured measles-specific T cells.ResultsAmong 750 infants (341 MMR, 409 placebo) in the cellular immunogenicity trial, a significant cellular immune response was observed one-month post-intervention in the MMR group compared to placebo (geometric mean ratio [GMR]: 12.3; 95% CI: 6.9–21.9). The cellular conversion rate (CCR) in the MMR group was 45%, comparable to the previously reported seroconversion rate. However, following routine MMR at 15 months, a reduced cellular response was observed in the early MMR group (GMR: 0.6; 95% CI: 0.3–0.9). Post-routine MMR, CCRs were 66% (MMR) and 74% (placebo). The immune conversion rate (ICR, defined as seroconversion and/or T-cell response) reached 99% in both groups post-routine MMR.ConclusionEarly MMR at 6 months elicited significant measles-specific cellular responses, though the CCR was lower than after routine MMR at 15 months. However, when combining serological and cellular responses, 99% of infants achieved immune conversion by 15 months. Early MMR could help reduce measles burden in infants in endemic settings without compromising subsequent immunizations.Clinical trial registrationClinicalTrials.gov, identifier NCT03780179, EudraCT 2016-001901-18.